A high-adhesion, low-swelling mussel-mimetic tissue adhesive, its preparation method and application

CN122230085BActive Publication Date: 2026-10-30IMEIK TECH DEV CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610393261.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-03-27
Publication Date
2026-10-30
Estimated Expiration
2046-03-27

AI Technical Summary

Technical Problem

首先,如何通过化学修饰制备得到高儿茶酚含量的粘合剂基材以充分发挥儿茶酚基团的粘附性能仍存在困难

Benefits of technology

(1)本发明基于高儿茶酚接枝率的聚赖氨酸衍生物粘合基材,合理调整其与多臂聚乙二醇衍生物的浓度和体积配比设计,在粘合界面发生原位交联反应,形成高密度、不同力学梯度的粘合位点,通过利用基团间的疏水相互作用、儿茶酚的“仿贻贝”粘合和NHS活性酯或醛基化学反应等多机制的协同作用,可以显著提升组织粘合剂整体的粘合强度,即时粘合强度最高可达114.6kPa;另外,组织粘合剂中高的儿茶酚含量,在长期湿润环境中可通过自氧化形成邻苯醌,可进一步与被粘附材料偶联,增强交联和粘附密度以提高胶体结构稳定性,并能避免过度溶胀,大大提高了胶体与组织间的长效粘合能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122230085B_ABST
    Figure CN122230085B_ABST
Patent Text Reader

Abstract

The application discloses a kind of high adhesive force, low swelling type imitation mussel tissue adhesive and its preparation method and application.The tissue adhesive includes polylysine derivative containing catechol side group and multi-arm polyethylene glycol derivative, and the polylysine derivative containing catechol side group is obtained by grafting reaction of catechol acid and polylysine or its salt through double solvent step-by-step coupling process.The tissue adhesive is prepared based on the adhesive substrate of high catechol grafting rate and specific in-situ gelation method, and the obtained imitation mussel tissue adhesive shows the characteristics of high adhesive force, low swelling and durable adhesion, immediate bonding strength exceeds 110kPa, and has good application prospect in postoperative tissue adhesion, sealing and hemostasis etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical materials technology, specifically relating to a high-adhesion, low-swelling mussel-like tissue adhesive, its preparation method, and its application. Background Technology

[0002] The World Health Organization estimates that more than 230 million major surgical procedures are performed worldwide each year. Traditional surgery primarily uses sutures, staples, rivets, wires, and medical tape for mechanical fixation. In recent years, laparoscopic surgery has rapidly gained popularity, and it is projected that by 2030, laparoscopic surgery will account for more than 50% of all surgeries in China. Traditional sutures are limited by the confined space of a laparoscope and cannot keep up with the new trends in laparoscopic surgery. Furthermore, in the sealing of fragile organs such as the lungs, liver, spleen, and kidneys, sutures and staples may cause secondary trauma and increase the risk of infection; while in organs requiring strict sealing, such as the dura mater, lungs, pancreas, gallbladder, and gastrointestinal tract, the use of sutures and staplers not only fails to achieve complete wound sealing, but the resulting secondary trauma points and prolonged stress concentration can also lead to serious gas and fluid leakage. Against this backdrop, tissue adhesives, as a novel medical device, are gradually entering clinical application and demonstrating unique advantages. Compared with traditional surgical closure methods, the use of tissue adhesives can achieve water seal, reduce the risk of gas and liquid leakage, reduce the occurrence of complications, and significantly shorten the time for surgery and wound healing, reduce additional trauma, and alleviate patient suffering.

[0003] From a material composition perspective, commercially available tissue adhesives are mainly fibrin-based, polyethylene glycol-based, and cyanoacrylate-based. Fibrin-based adhesives have low bonding strength, making them unable to withstand intra-organ pressure and unsuitable for tissue sealing, primarily used for hemostasis. Cyanoacrylate adhesives are limited in widespread application due to concerns about irritation and the cytotoxicity of their degradation products. Polyethylene glycol tissue adhesives based on multi-arm polyethylene glycol-N-hydroxysuccinimide esters exhibit better biocompatibility and have achieved high adoption rates in some developed countries. Based on the "NHS active ester chemistry" mechanism, multi-arm polyethylene glycol-N-hydroxysuccinimide esters can crosslink in situ with amino-containing adhesive substrates to form a gel, and react with amino groups on the tissue surface to form amide bonds, achieving tissue adhesion. For example, Chinese invention patent CN115869456A discloses the preparation of an in-situ gelled, anti-swelling, and enhanced tissue adhesive material. It involves dissolving terminally modified active ester multi-arm polyethylene glycol and modified catechol-based primary amino polymers using buffer solution, then mixing and applying or injecting the mixture into wound tissue for adhesion or closure. Although the tissue adhesion has been proven effective, the grafting rate of the catechol modification is low, only 16%, and the immediate adhesive strength is 52 kPa. The limited adhesive mechanism is the main reason for the limited performance of existing adhesive products. Combining the advantages of the in-situ reaction of multi-arm polyethylene glycol-N-hydroxysuccinimide ester with a new adhesive mechanism to synergistically improve adhesive performance is key to solving the clinical effectiveness of tissue adhesives.

[0004] In nature, marine organisms such as mussels can firmly adhere to underwater rock surfaces. Research has found that this is due to an adhesion protein (MAP) secreted by mussels, rich in 3,4-dihydroxyphenylalanine (DOPA) residues. The catechol groups in DOPA are chemically active, possessing lone pairs of electrons. These groups can accept hydrogen atoms from hydrogen donors or donate hydrogen atoms to other active groups, enabling them to interact chemically or physically with various substances, including hydrogen bonds, metal-catechin coordination bonds, etc. effect, Cationic interactions, oxidative crosslinking, and electrostatic interactions are all involved. Extensive research in recent years has confirmed the enormous adhesive potential of catechols. Chemically modified catechol-containing mussel-like tissue adhesives hold promise for solving the current problem of suboptimal adhesive performance. However, these mussel-like tissue adhesives still face two key challenges. First, obtaining adhesive substrates with high catechol content through chemical modification to fully utilize the adhesive properties of catechol groups remains difficult. Because small molecule compounds containing catechols (such as dopamine, 3,4-dihydroxyphenylpropionic acid, and DOPA) are easily oxidized and deactivated, and the intermediates used in synthesis have poor solubility, it is difficult to modify catechol groups in large quantities on the substrate. From the current technology, catechol-containing adhesive substrates constructed based on chemical modification strategies generally struggle to improve the catechol grafting rate. Second, effectively utilizing catechol-containing substrates to construct tissue adhesives based on in-situ crosslinking technology to achieve significant improvements in comprehensive properties such as tissue adhesion and anti-swelling remains a challenge.

[0005] Based on the above background, there is a need to develop adhesive substrates with high catechol content and to study methods for constructing high-performance mussel-like tissue adhesives using catechol-containing adhesive substrates, so as to achieve better applications in postoperative tissue adhesion and sealing. Summary of the Invention

[0006] To overcome the problems in existing technologies, this invention provides a high-adhesion, low-swelling mussel-like tissue adhesive, its preparation method, and its applications. A polylysine derivative with a high catechol grafting rate is prepared using dual-solvent stepwise coupling technology (DSCT) as the adhesive substrate. Then, this polylysine derivative with a high catechol grafting rate is mixed with a multi-arm polyethylene glycol derivative and reacted to obtain the tissue adhesive. After being applied to the tissue surface, this adhesive can crosslink in situ to form a tough gel, exhibiting high adhesion, low swelling, and long-lasting adhesion. It can be used in postoperative tissue adhesion, sealing, anti-adhesion, and radiotherapy isolation applications.

[0007] In a first aspect, the present invention provides a high-adhesion, low-swelling mussel-like tissue adhesive, the tissue adhesive comprising a polylysine derivative containing catechol side groups and a multi-arm polyethylene glycol derivative, wherein the polylysine derivative containing catechol side groups is obtained by grafting catechol acid with polylysine or its salts through a two-solvent stepwise coupling process.

[0008] Furthermore, the catecholic acid is selected from one or more of 3,4-dihydroxyphenylpropionic acid (DHCA), 3,4-dihydroxybenzoic acid, 3,4-dihydroxyphenylacetic acid, 2,3-dihydroxybenzoic acid, and 3,4-dihydroxycinnamic acid.

[0009] In some embodiments of the present invention, the catecholic acid is DHCA or 3,4-dihydroxycinnamic acid.

[0010] Furthermore, the polylysine is Polylysine ( One or more of poly-L-lysine (PLL), hyperbranched poly-L-lysine (HPL), and dendritic poly-L-lysine (DPL); preferably Polylysine ( One or both of the following: ) and hyperbranched polylysine (HPL).

[0011] Furthermore, the dual-solvent stepwise coupling process involves dispersing catecholic acid in the organic phase, polylysine or its salt in the aqueous phase, and then performing a grafting reaction.

[0012] Furthermore, the multi-arm polyethylene glycol derivative is a functionalized multi-arm polyethylene glycol, wherein the number of arms of the multi-arm polyethylene glycol is 2-8; preferably 4.

[0013] Furthermore, the multi-arm polyethylene glycol derivative is a multi-arm polyethylene glycol NHS active ester or a multi-arm polyethylene glycol aldehyde derivative.

[0014] Furthermore, the weight-average molecular weight of the multi-arm polyethylene glycol is 5-20 kDa, preferably 10-20 kDa.

[0015] Further, the end groups of the multi-arm polyethylene glycol NHS active ester include one or more of succinimide nonanoate (SAZ), succinimide hexanoate (SAP), succinimide carbonate (SC), succinimide acetate (SCM), succinimide glutarate (SG), and succinimide succinate (SS); preferably SG and SS.

[0016] Furthermore, the end groups of the multi-arm polyethylene glycol aldehyde derivative include one or both of butyraldehyde (bALD) and o-phthalaldehyde (OPA); preferably OPA.

[0017] A second aspect of the present invention provides a method for preparing a high-adhesion, low-swelling mussel-like tissue adhesive, the method comprising the following steps: S1. Prepare a polylysine derivative solution containing catechol side groups; S2. Prepare a multi-arm polyethylene glycol derivative solution; S3. Mix the polylysine derivative solution containing catechol side groups and the multi-arm polyethylene glycol derivative solution to obtain the tissue adhesive.

[0018] Further, in step S1, the concentration of the polylysine derivative containing the catechol side group in the solution is 30-300 mg / mL.

[0019] Furthermore, the solvent used in the solution is phosphate buffer, Tris buffer, sodium bicarbonate solution, or sodium tetraborate solution, etc.

[0020] Furthermore, the pH of the solvent is 9.0-12.6.

[0021] Further, in step S1, the method for preparing the polylysine derivative containing catechol side groups includes the following steps: (1) Dissolve catechol acid in the organic phase, then add N-hydroxysuccinimide (NHS), stir until dissolved and mixed, then add carbodiimide hydrochloride (EDC·HCl), stir to react, and obtain catechol-NHS intermediate solution. (2) Dissolve polylysine or its salt in the aqueous phase, and adjust the pH value to 5.5-7.4 using an alkaline solution to obtain a polylysine or its salt solution; (3) Add the intermediate solution obtained in step (1) to the polylysine or its salt solution obtained in step (2), and use an alkaline solution to maintain the pH of the reaction system at 4.5-6.5 to obtain a polylysine derivative containing catechol side groups.

[0022] Further, in step (1), the organic phase is selected from one or more of dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), 1,4-dioxane, tetrahydrofuran (THF), N-methylpyrrolidone (NMP), and N,N-dimethylacetamide (DMAC).

[0023] In some embodiments of the present invention, the organic phase is DMSO or a mixed solution of DMSO and DMF.

[0024] Further, in step (1), the mass concentration of the catechin acid in the organic phase is 10-200 mg / mL, specifically 10, 20, 30, 50, 90, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200 mg / mL, preferably 30-180 mg / mL.

[0025] Further, in step (1), the molar ratio of catecholic acid and EDC·HCl is 1:0.2-2, specifically 1:0.2, 1:0.4, 1:0.6, 1:0.8, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2.

[0026] In some embodiments of the present invention, the molar ratio of the catecholic acid and EDC·HCl is 1:1.

[0027] Further, in step (1), the molar ratio of NHS and EDC·HCl is 1:0.2-2, specifically 1:0.2, 1:0.4, 1:0.6, 1:0.8, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2.

[0028] In some embodiments of the present invention, the molar ratio of NHS and EDC·HCl is 1:1.

[0029] Furthermore, step (1) is performed under a protective atmosphere (such as nitrogen).

[0030] Furthermore, in step (1), the reaction temperature is room temperature, such as 20-30℃.

[0031] Further, in step (1), the reaction time is 5-100 min, specifically 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100 min, preferably 20-70 min. In some embodiments of the present invention, in step (1), the reaction time is 30 min.

[0032] Further, in step (2), the weight-average molecular weight of the polylysine or its salt is 2-10 kDa.

[0033] Further, in step (2), the mass concentration of the polylysine or its salt solution is 10-30 mg / mL, specifically 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, or 30 mg / mL. In some embodiments of the present invention, the mass concentration of the polylysine or its salt solution is 21.33 mg / mL.

[0034] Furthermore, in step (2), the aqueous phase is water, such as purified water or deionized water.

[0035] Further, in step (2), the pH value can be any value between 5.5 and 7.4, such as 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, and 7.4. In some embodiments of the present invention, in step (2), the pH value is 6.6 or 7.0.

[0036] Further, the molar ratio of the repeating unit in the catecholic acid and polylysine or its salt is 0.05-0.8:1, specifically such as 0.05:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1. In some embodiments of the present invention, the molar ratio of the catecholic acid and polylysine or repeating unit is 0.5:1 or 0.25:1.

[0037] Further, in step (3), the pH value can be any value between 4.5 and 6.5, specifically such as 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, and 6.5. In some embodiments of the present invention, in step (3), the pH value is 5.5 or 4.8.

[0038] Further, in steps (2)-(3), the alkaline solution is selected from one or more of sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution, potassium carbonate solution, sodium bicarbonate solution, potassium bicarbonate solution and triethylamine.

[0039] Further, the mass concentration of the alkaline solution is 1-10%, specifically such as 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, preferably 3-7.5%.

[0040] In some embodiments of the present invention, in steps (2)-(3), the alkaline solution is a 5% sodium hydroxide solution.

[0041] Furthermore, in step (3), the reaction temperature is room temperature, such as 20-30℃.

[0042] Furthermore, in step (3), the reaction time is 0.5-3h, specifically 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, preferably 1-2h.

[0043] In some embodiments of the present invention, the reaction time in step (3) is 2 hours.

[0044] In existing technologies, the grafting and coupling modification of polylysine or its salts by catechol acids is based on an amidation reaction. Taking DHCA as an example, EDC·HCl and NHS are typically used as activators, and the reaction mechanism is shown in the figure below. In this reaction, EDC·HCl first reacts with DHCA to form the active intermediate DHCA-EDC, which then reacts with NHS to generate DHCA-NHS. Currently reported reactions of DHCA with polylysine or its salts are almost all carried out in aqueous or organic phase systems. In aqueous phase synthesis, the reaction efficiency is low due to the easy hydrolysis of DHCA-EDC and the poor solubility of DHCA-NHS, resulting in low grafting rates and low raw material conversion rates. In organic phase synthesis, although the hydrolysis of DHCA-EDC and the poor solubility of DHCA-NHS are reduced, the poor solubility of polylysine or its salts in the organic phase also limits the reaction efficiency, resulting in low grafting rates of the final product.

[0045] To address the aforementioned issues, this invention implements the preparation of DHCA-NHS and the coupling of DHCA-NHS with polylysine or its salts in separate steps within different solution systems. The synthesis of DHCA-NHS is carried out in the organic phase. After obtaining a relatively stable DHCA-NHS solution, it is then added to the aqueous phase for coupling with polylysine or its salts. This stepwise coupling reaction using both organic and aqueous phases avoids the hydrolysis of the DHCA-EDC intermediate during DHCA-NHS synthesis. Furthermore, the solubility of DHCA-NHS is addressed by the co-solvent effect of the organic solvent in the organic phase after its addition to the aqueous phase. Simultaneously, the aqueous phase ensures good dissolution of polylysine or its salts. Ultimately, this maximizes reaction efficiency during the amidation reaction, effectively improving the grafting rate and DHCA conversion rate of the product.

[0046] Furthermore, the inventors discovered through research that the order of adding NHS first for dispersion and then adding EDC·HCl in step (1) is crucial. This is because EDC reacts quickly with DHCA. By dispersing NHS in DHCA first, the side reactions between the highly active intermediate product DHCA-EDC formed during the reaction and the phenolic hydroxyl groups on the DHCA molecule can be effectively reduced, thereby improving the synthesis efficiency of DHCA-NHS ester.

[0047] If EDC·HCl is added first, a side reaction will quickly occur in the solution, turning it wine-red. This may be because after EDC·HCl reacts with DHCA to form DHCA-EDC, in the absence of NHS in the solution, DHCA-EDC will undergo a side reaction with the phenolic hydroxyl groups on the DHCA molecule, thus causing the solution to turn wine-red.

[0048] Furthermore, if EDC·HCl and NHS are added simultaneously, although the solution color does not change significantly, the grafting rate of the final product is still lower compared to the product obtained by adding NHS first and then EDC·HCl. This may be because the reaction between EDC and DHCA is rapid, and the resulting DHCA-EDC has high activity. Before NHS is completely and uniformly dispersed, the highly active DHCA-EDC will still undergo a small amount of side reaction with the phenolic hydroxyl groups on the DHCA molecules in the solution, thus affecting the grafting rate of the final product.

[0049] Furthermore, the preparation method also includes a post-processing step, which includes the following steps: dialysis, centrifugation and drying of the product obtained in step (3) to obtain a purified polylysine derivative containing catechol side groups.

[0050] Furthermore, the dialysate used in the dialysis is selected from hydrochloric acid, acetic acid, or citric acid.

[0051] Furthermore, the concentration of the dialysate is 0.1-0.5 mM.

[0052] In some embodiments of the present invention, the dialysate is hydrochloric acid with a concentration of 0.3 mM.

[0053] In some embodiments of the present invention, the dialysate is acetic acid with a concentration of 0.2 mM.

[0054] Furthermore, the dialysis time is 12-48 hours, specifically 12 hours, 18 hours, 24 hours, 30 hours, 36 hours, 42 hours, and 48 hours. In some embodiments of the present invention, the dialysis time is 24 hours.

[0055] Furthermore, the drying process is freeze drying.

[0056] In some embodiments of the present invention, the post-processing includes the following steps: dialyzing the product obtained in step (3) in 0.3 mM hydrochloric acid or 0.2 mM acetic acid, centrifuging after dialysis, taking the supernatant and freeze-drying it to obtain a purified polylysine derivative containing catechol side groups.

[0057] The inventors discovered that by using a weakly acidic system to dialyze the grafted product of polylysine derivatives containing catechol side groups, the oxidation of the catechol group in the catechol side group can be prevented, thereby improving the stability and adhesion of the product.

[0058] Furthermore, the grafting efficiency of the polylysine derivative containing catechin side groups is ≥90%.

[0059] Further, in step S2, the concentration of the multi-arm polyethylene glycol derivative in the solution is 100-300 mg / mL.

[0060] Furthermore, the solvent used in the solution is a phosphate buffer solution, a phosphoric acid solution, a hydrochloric acid solution, or an acetic acid solution, etc.

[0061] Further, the pH of the phosphate buffer solution is 5.0-7.4; the pH of the phosphate solution, hydrochloric acid solution or acetic acid solution is 5.0-6.5.

[0062] Further, in step S3, the volume ratio of the polylysine derivative solution containing catechol side groups to the multi-arm polyethylene glycol derivative solution is 1:0.8-3. After mixing, the solution is applied to the desired tissue site by means of smearing, spraying or injection to form a hydrogel that adheres to the tissue in situ.

[0063] The in-situ cross-linked gel formed based on the above steps can achieve immediate high tissue adhesion without interference from tissue surface moisture, and exhibits low swelling, stable adhesion, and good biocompatibility during long-term sealing. This tissue adhesive can be used to close surgical incisions to prevent liquid and gas leakage, and can also be used to control tissue bleeding, demonstrating high application value in the medical field.

[0064] A third aspect of the present invention provides the application of the high-adhesion, low-swelling mussel tissue adhesive described in the first aspect of the present invention or the high-adhesion, low-swelling mussel tissue adhesive prepared by the preparation method described in the second aspect of the present invention in the preparation of medical materials.

[0065] Furthermore, the medical material can be used in fields such as tissue adhesion, drug sustained release, tissue repair, anti-adhesion, and radiotherapy isolation.

[0066] The present invention has the following beneficial effects: (1) Based on the high catechol grafting rate of polylysine derivative adhesive substrate, the present invention rationally adjusts the concentration and volume ratio of the substrate and the multi-arm polyethylene glycol derivative to conduct an in-situ cross-linking reaction at the adhesive interface, forming high-density adhesive sites with different mechanical gradients. By utilizing the synergistic effect of multiple mechanisms such as hydrophobic interaction between groups, "mussel-like" adhesion of catechol and chemical reaction of NHS active ester or aldehyde, the overall adhesive strength of the tissue adhesive can be significantly improved, with the immediate adhesive strength reaching up to 114.6 kPa. In addition, the high catechol content in the tissue adhesive can form o-benzoquinone through self-oxidation in a long-term humid environment, which can further couple with the adhered material, enhance cross-linking and adhesion density to improve the stability of the colloidal structure, and avoid excessive swelling, greatly improving the long-term adhesion ability between the colloid and the tissue.

[0067] (2) This invention utilizes a two-solvent stepwise coupling technique to synthesize polylysine by coupling with catechol acid. First, catechol-NHS is synthesized in the organic phase to obtain a relatively stable catechol-NHS solution. Then, polylysine or its salt is dispersed in the aqueous phase, and the organic phase and the aqueous phase are mixed to carry out the coupling reaction. This not only avoids the hydrolysis of catechol-EDC and the precipitation of catechol-NHS in the aqueous phase, but also ensures the good solubility of polylysine or its salt, maximizing the utilization rate of EDC·HCl and NHS, effectively improving the reaction efficiency of the subsequent amidation reaction with polylysine or its salt, and increasing the grafting rate of polylysine-catechin. The grafting efficiency is as high as 90% or more. Attached Figure Description

[0068] Figure 1 The one prepared for Synthesis Example 1 Photograph of the sample's appearance (A) and its UV absorption spectrum (B).

[0069] Figure 2 The instant overlap-shear adhesion test curves (A) and instant adhesion strength (B) of the gelling formulations of Examples 1-8 and Comparative Examples 1-4 applied to the surface of pigskin tissue are shown.

[0070] Figure 3 The stress-strain curves (A), stress-strain curves (B, i.e., a magnified view of the red box in stress-strain curve A), and compression modulus diagrams (C) of the tissue adhesives obtained from the gelling formulations of Examples 1-8 and Comparative Examples 1-4 are shown.

[0071] Figure 4 The images show the tissue adhesive gels obtained in Examples 2, 6, and Comparative Examples 1-4 before and after swelling.

[0072] Figure 5 The water contact angle test diagrams are for the tissue adhesive gels obtained in Examples 2, 6, and Comparative Examples 1-2.

[0073] Figure 6 The long-term overlap-shear adhesion test curves (A) and long-term adhesion strength (B) of the gelling formulations of Examples 2, 6, and Comparative Examples 1-2 applied to the surface of pigskin tissue are shown. Detailed Implementation

[0074] Unless otherwise defined, all scientific and technical terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art.

[0075] The term "catechinic acid" refers to compounds formed by the combination of catechins and carboxyl groups, including but not limited to 3,4-dihydroxyphenylpropionic acid (DHCA, also known as dihydrocaffeic acid or hydrogenated caffeic acid), 3,4-dihydroxybenzoic acid, 3,4-dihydroxyphenylacetic acid, 2,3-dihydroxybenzoic acid, and 3,4-dihydroxycinnamic acid (also known as caffeic acid).

[0076] The term "grafting efficiency" is a parameter used to describe the ratio between the actual grafting extent and the maximum possible grafting extent in a polymer grafting reaction. It can be used to evaluate the efficiency of the grafting reaction, i.e., what percentage of the theoretical grafting points are utilized in the actual reaction.

[0077] The term "room temperature" refers to the temperature of an item that is close to or the same as the temperature of the space in which the item is located (e.g., the location of a fume hood where the item is situated). Typically, room temperature is from about 20°C to about 30°C, or from about 22°C to 27°C, or about 25°C.

[0078] For details regarding the process, advantages, and effects of the "dual-solvent stepwise coupling technology" of this invention, please refer to patent CN202411383465.X - A polylysine derivative containing catechol side groups and its preparation method and application.

[0079] All publications, patents, and published patent specifications cited in this article are incorporated herein in their entirety through citation.

[0080] The raw materials and reagents used in this embodiment and comparative example are all commercially available products.

[0081] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0082] Synthesis example 1 Under nitrogen protection, 180 mg of DHCA was weighed and added to 1.2 mL of DMSO, and stirred at room temperature until completely dissolved. 112 mg of NHS and 188 mg of EDC·HCl were weighed separately. NHS was added to the solution first and stirred until completely mixed before adding EDC·HCl. The reaction was stirred for 30 min to obtain the DHCA-NHS solution.

[0083] Weigh (MW=4kDa) was placed in a reaction flask, and 15mL of purified water was added and stirred until completely dissolved. DHCA and The molar ratio of the repeating unit was 0.5:1, and the pH was adjusted to 6.6 using 5% NaOH solution. The DHCA-NHS solution generated in the above reaction was added to the reaction system all at once, and the pH was adjusted to approximately 5.5 using 5% NaOH solution. The reaction was continued for 2 hours and then stopped. After the reaction, the system was a slightly yellow and transparent state. Dialysis was performed with 0.3 mM dilute hydrochloric acid for 24 hours. After dialysis, the product in the dialysis bag was transferred to a centrifuge tube, centrifuged, and the supernatant was lyophilized to obtain the product. After freeze-drying, the product is white and spongy, with the following specific morphology: Figure 1 As shown in (A), the absorption spectrum of the product solution was measured by ultraviolet spectrophotometry, and the results are as follows. Figure 1 As shown in (B). From Figure 1 (B) It can be seen that the absorption spectrum shows a characteristic absorption peak of the catechol group at 280 nm, indicating that DHCA has been successfully modified to [the desired effect]. Above. Calculated based on the absorbance value at 280nm. The grafting rate was 48.5%; the theoretical grafting rate was 50% based on the molar ratio of raw materials, and the grafting efficiency = actual grafting rate / theoretical grafting rate = 97.0%.

[0084] Synthesis example 2 Under nitrogen protection, 90 mg of DHCA was weighed and added to 1.2 mL of DMSO / DMF mixed solvent (volume ratio of 1:1), and stirred at room temperature until completely dissolved. 56 mg of NHS and 94 mg of EDC·HCl were weighed separately. NHS was added to the solution first and stirred until completely mixed before adding EDC·HCl. The reaction was stirred for 20 min to obtain the DHCA-NHS solution.

[0085] Weigh (MW=4kDa) was placed in a reaction flask, and 15mL of purified water was added and stirred until completely dissolved. DHCA and The molar ratio of the repeating unit was 0.25:1, and the pH was adjusted to 6.6 using 5% NaOH solution. The DHCA-NHS solution generated in the above reaction was added to the reaction system all at once, and the pH was adjusted to approximately 5.5 using 5% NaOH solution. After continuing the reaction for 2 hours, the reaction was stopped, and the mixture was dialyzed with 0.3 mM dilute hydrochloric acid for 24 hours. After dialysis, the product in the dialysis bag was transferred to a centrifuge tube, centrifuged, and the supernatant was lyophilized to obtain the product. Measured by ultraviolet spectrophotometry The grafting rate was 22.9%; the theoretical grafting rate was 25% based on the molar ratio of raw materials, and the grafting efficiency = actual grafting rate / theoretical grafting rate = 91.6%.

[0086] Synthesis example 3 Under nitrogen protection, 182 mg of 3,4-dihydroxycinnamic acid was weighed and added to 1.2 mL of DMSO. The mixture was stirred at room temperature until completely dissolved. 112 mg of NHS and 188 mg of EDC·HCl were weighed separately. NHS was added to the solution first and stirred until completely mixed. Then EDC·HCl was added and the mixture was stirred for 30 min to obtain a 3,4-dihydroxycinnamic acid-NHS solution.

[0087] Weigh 250 mg of poly-L-lysine (PLL) (MW=8 kDa) into a reaction flask, add 15 mL of purified water and stir until completely dissolved. 3,4-Dihydroxycinnamic acid and... The molar ratio of the repeating unit was 0.5:1, and the pH was adjusted to 7.0 using 5% NaOH solution. The 3,4-dihydroxycinnamic acid-NHS solution generated in the above reaction was added to the reaction system all at once, and the pH was adjusted to approximately 4.8 using 5% NaOH solution. After reacting for 3 hours, the reaction was stopped, and the mixture was dialyzed with 0.2 mM acetic acid for 24 hours. After dialysis, the product in the dialysis bag was transferred to a centrifuge tube, centrifuged, and the supernatant was lyophilized to obtain PLL-3,4-dihydroxycinnamic acid. The grafting rate of PLL-3,4-dihydroxycinnamic acid, determined by ultraviolet spectrophotometry, was 46.5%. Based on the molar ratio of the raw materials, the theoretical grafting rate was calculated to be 50%, and the grafting efficiency = actual grafting rate / theoretical grafting rate = 93.0%.

[0088] Synthesis example 4 Under nitrogen protection, 180 mg of DHCA was weighed and added to 1.2 mL of DMSO, and stirred at room temperature until completely dissolved. 112 mg of NHS and 225.6 mg of EDC·HCl were weighed separately. NHS was added to the solution first and stirred until completely mixed before adding EDC·HCl. The reaction was stirred for 30 min to obtain the DHCA-NHS solution.

[0089] 250 mg of HPL (MW = 9.8 kDa) was weighed and placed in a reaction flask. 15 mL of purified water was added and stirred until completely dissolved. The molar ratio of DHCA to the repeating unit in HPL was 0.5:1. The pH was adjusted to 6.6 using 5% NaOH solution. The DHCA-NHS solution generated in the above reaction was added to the above reaction system all at once. The pH of the system was adjusted to approximately 5.5 using 5% NaOH solution. The reaction was continued for 2 hours and then stopped. The mixture was dialyzed with 0.3 mM dilute hydrochloric acid for 24 hours. After dialysis, the product in the dialysis bag was transferred to a centrifuge tube and centrifuged. The supernatant was collected and lyophilized to obtain the product HPL-DHCA. The grafting rate of the product HPL-DHCA was determined to be 45.8% by UV spectrophotometry. Based on the molar ratio of the raw materials, the theoretical grafting rate was calculated to be 50%, and the grafting efficiency = actual grafting rate / theoretical grafting rate = 91.6%.

[0090] Synthetic Comparative Example 1 The only difference in Synthesis Example 1 is that "weighing 180 mg DHCA and adding it to 1.2 mL DMSO" is replaced with "weighing 180 mg DHCA and adding it to 1.2 mL purified water." All other steps are the same as in Synthesis Example 1, and the resulting product is... Measured by ultraviolet spectrophotometry The grafting rate was 27.6%. Based on the molar ratio of raw materials, the theoretical grafting rate was 50%, and the grafting efficiency = actual grafting rate / theoretical grafting rate = 55.2%.

[0091] Synthetic Comparative Example 2 In Synthesis Example 1, replace "add 15 mL of purified water and stir until completely dissolved" with "add 15 mL of DMSO and stir until completely dissolved," and omit the step of "adjusting the pH to 6.6 using 5% NaOH solution." All other steps are the same as in Synthesis Example 1. The resulting product is... Measured by ultraviolet spectrophotometry The grafting rate was 32.9%. Based on the molar ratio of raw materials, the theoretical grafting rate was 50%, and the grafting efficiency = actual grafting rate / theoretical grafting rate = 65.8%. Example 1

[0092] The result of synthesis example 1 Dissolved in PBS buffer at pH 12.6, yielding 200 mg / mL. Solution A: Dissolve 4-arm-PEG-SG (MW=10kDa) in PBS buffer at pH 7.4 to obtain 200mg / mL 4-arm-PEG-SG solution B; Mix solution A and solution B at a volume ratio of 1:0.8 to obtain a tissue adhesive, which is then applied to the desired tissue surface to form a gel through in-situ cross-linking. Example 2

[0093] The only difference is that in Example 1, "solution A and solution B are in a volume ratio of 1:0.8" is replaced with "solution A and solution B are in a volume ratio of 1:1", and the total volume of solution A and solution B is the same as in Example 1. All other steps are the same as in Example 1 to obtain a tissue adhesive, which is then applied to the desired tissue surface and crosslinked in situ to form a gel. Example 3

[0094] The only difference is that in Example 1, "solution A and solution B are in a volume ratio of 1:0.8" is replaced with "solution A and solution B are in a volume ratio of 1:2", and the total volume of solution A and solution B is the same as in Example 1. All other steps are the same as in Example 1 to obtain a tissue adhesive, which is then applied to the desired tissue surface and crosslinked in situ to form a gel. Example 4

[0095] The only difference is that in Example 1, "solution A and solution B are in a volume ratio of 1:0.8" is replaced with "solution A and solution B are in a volume ratio of 1:3", and the total volume of solution A and solution B is the same as in Example 1. All other steps are the same as in Example 1 to obtain a tissue adhesive, which is then applied to the desired tissue surface and crosslinked in situ to form a gel. Example 5

[0096] The HPL-DHCA obtained in Synthesis Example 4 was dissolved in sodium tetraborate buffer at pH 9.0 to obtain a 50 mg / mL HPL-DHCA solution A; 4-arm-PEG-SS (MW=15 kDa) was dissolved in PBS buffer at pH 6.5 to obtain a 150 mg / mL 4-arm-PEG-SG solution B; solutions A and B were mixed evenly at a volume ratio of 1:1, and the total volume of solutions A and B was consistent with that in Example 1 to obtain a tissue adhesive, which was then applied to the desired tissue surface to form a gel through in-situ crosslinking.

[0097] Example 6 The result of synthesis example 1 Dissolved in PBS buffer at pH 12.6, yielding 200 mg / mL. Solution A: 4-arm-PEG-OPA (MW=10kDa) was dissolved in acetic acid solution with pH 5.6 to obtain 100mg / mL 4-arm-PEG-OPA solution B; Solution A and Solution B were mixed evenly at a volume ratio of 1:1, and the total volume of Solution A and Solution B was consistent with that in Example 1 to obtain a tissue adhesive, which was then applied to the desired tissue surface to form a gel through in-situ crosslinking. Example 7

[0098] The PLL-3,4-dihydroxycinnamic acid obtained in Synthesis Example 3 was dissolved in Tris buffer at pH 11.0 to obtain 250 mg / mL. Solution A: 4-arm-PEG-SG (MW=20kDa) was dissolved in hydrochloric acid solution with pH 5.0 to obtain 250mg / mL 4-arm-PEG-SG solution B; Solution A and Solution B were mixed evenly at a volume ratio of 1:1, and the total volume of Solution A and Solution B was consistent with that in Example 1 to obtain a tissue adhesive, which was then applied to the desired tissue surface to form a gel through in-situ crosslinking. Example 8

[0099] The result from Synthesis Example 2 Dissolved in PBS buffer at pH 12.6, yielding 200 mg / mL. Solution A: Dissolve 4-arm-PEG-SG (MW=10kDa) in PBS buffer at pH 7.4 to obtain 200mg / mL 4-arm-PEG-SG solution B; Mix solution A and solution B at a volume ratio of 1:1 until homogeneous, and ensure that the total volume of solution A and solution B is consistent with that in Example 1 to obtain a tissue adhesive, which is then applied to the desired tissue surface to form a gel through in-situ crosslinking.

[0100] Comparative Example 1 Only the "synthetic example 1 obtained" in Example 2 Replace with "the result of synthetic comparative example 1" The total volume of solutions A and B is the same as in Example 2, and the remaining steps are the same as in Example 2. A tissue adhesive is obtained and then applied to the desired tissue surface to form a gel through in-situ crosslinking.

[0101] Comparative Example 2 Only the "synthetic example 1 obtained" in Example 2 Replace with "the result of synthetic comparative example 2" The total volume of solutions A and B is the same as in Example 2, and the remaining steps are the same as in Example 2. A tissue adhesive is obtained and then applied to the desired tissue surface to form a gel through in-situ crosslinking.

[0102] Comparative Example 3 The only difference is that in Example 2, "solution A and solution B are in a volume ratio of 1:0.8" is replaced with "solution A and solution B are in a volume ratio of 1:0.5", and the total volume of solution A and solution B is the same as in Example 2. All other steps are the same as in Example 2 to obtain a tissue adhesive, which is then applied to the desired tissue surface and crosslinked in situ to form a gel.

[0103] Comparative Example 4 The only difference is that in Example 2, "solution A and solution B are in a volume ratio of 1:0.8" is replaced with "solution A and solution B are in a volume ratio of 1:4", and the total volume of solution A and solution B is the same as in Example 2. All other steps are the same as in Example 2 to obtain a tissue adhesive, which is then applied to the desired tissue surface and crosslinked in situ to form a gel.

[0104] Performance example 1 After thawing, the pigskin tissue was processed according to ASTM F2255 and cut into rectangular samples of 1.5cm × 3cm. These samples were then fixed to glass slides using 502 glue. Following the gel formulations of Examples 1-8 and Comparative Examples 1-4, solutions A and B were rapidly mixed and applied to an area of ​​approximately 1.5cm × 1cm on one end of the pigskin sample surface in the corresponding proportions (total volume: Another piece of pigskin was overlapped in this area, and approximately 50 mg of material was applied for 5 minutes, followed by a resting period of 10 minutes. The sample was then tested using a tensile testing machine according to ASTM F2255. All tests were conducted at a constant tensile speed of 5 mm / min. After the test, the maximum load during the test was recorded, and the bonded area of ​​the sample was measured. The instantaneous overlap-shear bond strength (i.e., instantaneous bond strength) of the tissue adhesive was determined by dividing the maximum load by the bonded area. The instantaneous overlap-shear bond test curve is shown below. Figure 2 (A) and instant bond strength as Figure 2 As shown in (B), the specific instantaneous adhesive strength data are shown in Table 1.

[0105] In addition, following the gel formulations of Examples 1-8 and Comparative Examples 1-4, solutions A and B were blended in a cylindrical silicone mold according to their respective proportions, and in-situ crosslinking was performed at room temperature to obtain gel samples. The resulting gel samples were placed at the center of the lower clamp surface of a tensile testing machine, and a small preload (0~0.05N) was applied so that the upper clamp surface just contacted the sample and remained stable. This position was recorded as point 0. The load was then applied using a displacement-controlled method at a loading speed of 1mm / min until the sample height reached 60% (approximately 1.2mm). The stress-strain curves for this process were recorded as follows: Figure 3 (A, B, where) Figure 3 B is Figure 3 As shown in the enlarged view within the box in section A, the compressive modulus is the slope of the stress-strain curve within the range of 15% to 25%. The test results are as follows: Figure 3 As shown in (C), the specific compression modulus data are shown in Table 1.

[0106] Table 1. Results of instant adhesive strength and compressive modulus for different gel samples from Figure 1-2As can be seen from Table 1, the tissue adhesives prepared from different types of catechol acids, NHS active esters, aldehydes, and other multi-arm polyethylene glycol derivatives in Examples 1-8 all exhibit high immediate adhesive strength. Furthermore, when the catechol grafting rate is 48.5%, the immediate adhesive strength of Example 3 can reach the highest of 114.6 kPa. By adjusting the gelation ratio of solution A and solution B in the tissue adhesive, the gel mechanical properties and immediate adhesive strength can be adjusted. As in Comparative Example 3 and Examples 1-4, with the increase of the volume of the multi-arm polyethylene glycol, when the volume ratio of solution A to solution B gradually increases from 1:0.5 to 1:0.8, 1:1, and 1:2, the compressive modulus and instantaneous adhesive strength of the gel gradually increase. This is because as the volume of PEG increases, the PEG content increases, and the NHS content also increases. On the one hand, this enhances the adhesion between the PEG and the tissue interface, thus increasing the instantaneous adhesive strength; on the other hand, the increase in NHS increases the degree of cross-linking of the gel and strengthens the gel cohesion, thereby increasing the compressive modulus. However, when the volume ratio continues to increase to 1:3, the continued increase in PEG will, to some extent, offset the increase in NHS content. The increased adhesive strength resulted from the increased adhesive strength, but the compressive modulus and adhesive strength of the resulting colloid decreased, indicating that the optimal immediate adhesive strength could be achieved by optimizing the volume ratio to 1:2. When the gelation ratio continued to increase to 1:4 (as in Comparative Example 4), the excess flexible PEG chains in the gelation system played a plasticizing and diluting role, further reducing the cohesive force and compressive modulus of the resulting colloid. Even though the gel itself contained more NHS adhesive groups in this gelation system, which could form a strong bond with the interface of the adhered tissue, the low cohesive force of the gel itself meant that during the adhesive shear failure process, the low cohesive force would preferentially cause failure from the inside of the gel, resulting in low immediate adhesive strength. In addition, it can also be seen from Examples 5-7 that, under the same gelation ratio, by adjusting the concentrations of solution A and solution B, the compressive modulus and immediate adhesive strength of the resulting tissue adhesive can be adjusted simultaneously to meet the needs of different application scenarios.

[0107] Furthermore, the results of the colloidal adhesion strength tests in Example 2 and Comparative Examples 1-2 show that, under the same gelation ratio, the higher the grafting rate of catechol groups in PL-DHCA, the higher the instantaneous adhesion strength of the adhesive. This is because, during the in-situ gelation process, in addition to the adhesion effect brought by the NHS active ester, catechol also forms effective chemical bonds with the tissue surface, while enhancing the hydrophobicity of the gel. Therefore, when adhering to a moist tissue surface, the hydrophobicity brought by the catechol groups can eliminate interfacial water on the tissue surface, exposing more adhesion groups, resulting in higher adhesion strength. Therefore, in Example 2, the DHCA-NHS solution was first prepared in the organic phase and then added to the aqueous phase. The stepwise coupling technique using two solvents in the reaction can prepare PL-DHCA with a grafting rate of 48.5%, resulting in a tissue adhesive with a high immediate bond strength of 93.4 kPa. In contrast, the grafting coupling reaction in Comparative Example 1 was carried out in an aqueous phase. The resulting DHCA-EDC exhibited poor stability and was prone to hydrolysis, leading to a low yield of the DHCA-NHS intermediate. Furthermore, its poor solubility in the aqueous phase resulted in significant precipitation, resulting in a low PL-DHCA grafting rate of only 27.6% and an immediate bond strength of 70.7 kPa, significantly lower than that of Example 2. The grafting coupling reaction in Comparative Example 2 was carried out in an organic phase. While the organic phase effectively prevented the hydrolysis of DHCA-EDC and the precipitation of the intermediate DHCA-NHS, the organic phase system also brought about… The problem of poor solubility ultimately leads to free... The limited collisions between molecules and DHCA-NHS molecules also greatly reduce the probability of collisions between carboxyl and amino groups, resulting in a decrease in the grafting rate of PL-DHCA. The grafting rate is 32.9%, and the instantaneous adhesive strength is 80.2 kPa, which is also lower than the instantaneous adhesive strength of Example 2.

[0108] Performance example 2 Following the gel formulations of Examples 2, 6, and Comparative Examples 1-4, solutions A and B were blended in a cylindrical silicone mold according to their respective proportions and crosslinked in situ at room temperature to obtain gel samples. The initial weight (W0) of the obtained gels was recorded. The gels were placed in 50 mL centrifuge tubes, and 20 mL of PBS buffer (10 mM, pH=7.4) was added. The tubes were sealed and placed at 37 °C for swelling. After 24 h, the samples were removed, excess water was wiped off with absorbent paper, and the weight was recorded as the mass (W1) after swelling. The swelling rate was calculated using the following formula: Swelling rate (%) = (W1-W0) / W0 × 100%. The swelling rate results are shown in Table 2 below, where the images of the obtained gels before and after swelling are shown in the figure. Figure 4 As shown.

[0109] Table 2. Swelling rate data of different gel samples From Table 2 and Figure 4As can be seen, the tissue adhesives formed by multi-arm polyethylene glycol derivatives containing NHS active esters or aldehyde groups and polylysine derivatives with high catechol content (such as in Examples 2 and 6) all exhibit very low swelling. This is mainly because the polylysine derivatives have a high catechol grafting rate and high catechol content. During the soaking process at 37°C, the soaking environment can accelerate the auto-oxidative cross-linking reaction of catechols. After the catechols are oxidized to o-benzoquinone, they form Schiff base bonds with amino groups and phenol-quinone coupling bonds with other catechols, supplementing the amidation cross-linking to form a dense network that hinders the penetration of water molecules, thus resulting in a lower swelling rate.

[0110] Furthermore, as shown in Table 2, under the same solution concentration, the different grafting rates of PL-DHCA catechols used in the gelling systems of Example 2 and Comparative Examples 1-2 resulted in significant differences in the swelling rates of the resulting gels. The swelling rate of the gel in Example 2 was -2.8%, while the swelling rates of the gels in Comparative Examples 1-2 were 47.9% and 31.8%, respectively. This indicates that the gel in Example 2 did not absorb any water during the swelling process, while Comparative Examples 1-2 all exhibited significant swelling. This is because the grafting rate of catechols in the polylysine derivative in Example 2 was high, resulting in a low swelling rate. In contrast, the grafting rate of catechols in the polylysine derivative in Comparative Examples 1-2 was low, and its content was relatively low. Therefore, the number of Schiff base bonds and coupling bonds formed was limited, leading to a looser network formed by the final cross-linking, thus resulting in a high swelling rate.

[0111] Furthermore, the swelling properties of Comparative Examples 3 and 4 also showed significant differences compared to Example 2. In Comparative Example 3, the swelling rate was -16.7%, significantly lower than -2.8% in Example 2. This is because, under the same total volume, when the volume ratio of solution A to solution B increased from 1:1 in Example 2 to 1:0.5 in Comparative Example 3, the catechol content further increased, leading to an excessively dense cross-linked network. Therefore, during swelling, the colloid would shrink significantly, and this shrinkage would damage the bonding interface, thereby reducing adhesion.

[0112] Similarly, in Comparative Example 4, the volume ratio of solution A to solution B is 1:4. Compared with the 1:1 ratio in Example 2, the multi-arm polyethylene glycol in Comparative Example 4 is significantly excessive. Multi-arm polyethylene glycol is highly hydrophilic and absorbs water more easily, resulting in a high swelling rate of the colloid (44.7%). Furthermore, the excessive flexible polyethylene glycol chains play a plasticizing and diluting role, reducing the cohesive force of the resulting colloid and thus reducing its adhesiveness.

[0113] The above conclusions can also be drawn from... Figure 4The comparison photos of the gels before and after swelling show that the gels in Examples 2 and 6 remained essentially unchanged in size after swelling, while the gels in Comparative Examples 1-2 and 4 showed a significant increase in volume after swelling, indicating that the gels absorbed water during swelling, thus increasing their volume. The gel in Comparative Example 3 showed a significant decrease in volume after swelling, indicating that the gel expelled water during swelling, thus decreasing its volume.

[0114] Performance Example 3 Following the gel formulations of Examples 2, 6, and Comparative Examples 1-2, solutions A and B were blended in a cylindrical silicone mold according to their respective proportions, and in-situ crosslinking was performed at room temperature to obtain a gel sample. A drop of [unclear text - possibly a typo] was then added to the gel surface. Purified water was photographed at the same height as the gel surface on the side of the water droplet, and the contact angle was measured using a protractor. The test results are shown in Table 3. The water contact angle test images are shown below. Figure 5 As shown.

[0115] Table 3. Hydrophilicity and hydrophobicity characterization results of different gel samples From Table 3 and Figure 5 It can be seen that the water contact angles of the gel surfaces in Examples 2 and 6 are 98° and 95°, respectively, indicating that, under the same catechol grafting rate, the tissue adhesive gels obtained with different multi-arm polyethylene glycol derivatives all exhibit good hydrophobicity. In contrast, the water contact angles of the gels obtained in Comparative Examples 1 and 2 are 53° and 67°, respectively, showing poor hydrophobicity compared to Example 2. This is because the gelling system used in Example 2... The high grafting rate of catechol groups in the medium-sized gel increases the hydrophobicity of the resulting colloid after gelation with 4-arm-PEG-SG solution in the same proportion. The higher the hydrophobicity of the gel, the more effectively it can remove interfacial water from the tissue surface during the adhesion process with the tissue interface, thus promoting interfacial adhesion.

[0116] Performance Example 4 Long-term adhesive stability refers to the mechanical adhesive ability that can be maintained and resist tissue separation under physiological microenvironment over a relatively long period of time (far exceeding immediate initial adhesion, usually several hours to several weeks, depending on the clinical application scenario). It is a core mechanical performance indicator for measuring the long-term adhesive stability of adhesives and adapting to the clinical needs of long-term tissue bonding.

[0117] After thawing, the pigskin tissue was processed according to ASTM F2255 and cut into rectangular samples of 1.5cm × 3cm. These samples were then fixed to a glass slide using 502 glue. Following the gel formulations selected for testing Examples 2, 6, and Comparative Examples 1-2, solutions A and B were rapidly mixed and applied to an area of ​​approximately 1.5cm × 1cm on one end of the pigskin sample surface in the corresponding proportions (total volume: Another piece of pigskin was overlapped in this area, and approximately 50 mg of material was applied and pressed for 5 minutes. The mixture was then left to stand for 10 minutes. The overlapped test sample was then sealed and immersed in PBS buffer (10 mM, pH 7.4) containing 0.02% sodium azide at 37°C for 14 days. After 14 days, the sample was removed from the liquid environment and dried. Tensile testing was then performed according to ASTM F2255. All tests were conducted at a constant tensile speed of 5 mm / min. After the tests, the maximum load was recorded and the bonded area of ​​the sample was measured. The long-term overlap-shear bond strength (i.e., long-term bond strength) was determined by dividing the maximum load by the bonded area. The long-term overlap-shear test curve and long-term bond strength are shown below. Figure 6 As shown in (A, B), the specific long-term adhesive strength data are shown in Table 4.

[0118] Table 4. Results of long-term adhesive strength of different gel samples from Figure 6As shown in Table 4, after 14 days of prolonged immersion, both the tissue and gel exhibited partial degradation. The tissue adhesive in Example 2 decreased from an immediate adhesive strength of 93.4 kPa to a long-term adhesive strength of 55.9 kPa, a decrease of approximately 40.1%. The tissue adhesive in Example 6 decreased from an immediate adhesive strength of 83.7 kPa to a long-term adhesive strength of 50.4 kPa, a decrease of approximately 39.8%. In contrast, the gels in Comparative Examples 1 and 2 decreased from immediate adhesive strengths of 70.7 kPa and 80.2 kPa to 19.7 kPa and 35.1 kPa, respectively, representing decreases of 72.1% and 56.2%. The decrease in adhesive strength in Comparative Examples 1 and 2 was greater than that in Example 2. Furthermore, the long-term adhesive strength of Example 2 was tested under a 14-day continuous immersion environment without changing the buffer solution. The unreplaced buffer solution contained enzymes and different... Impurities such as degradation products can lead to gel degradation, making the gel more closely resemble real-world usage environments. The resulting long-term adhesive strength test result (55.9 kPa) is significantly higher than the 20-40 kPa adhesive strength of commonly used tissue adhesives on the market. This is mainly due to the high catechin grafting rate of polylysine in this invention. The high catechin grafting rate (48.5% grafting rate and 97.0% grafting efficiency of polylysine derivative in Synthesis Example 1) has several advantages. First, the self-oxidation of catechins enhances the internal cross-linking network of the gel. The dynamically reversible bonds formed can eliminate stress concentration, giving the network both rigidity and toughness. At the same time, the oxidation of catechin groups to quinones can form continuous bonds with the tissue interface, resulting in a stable cross-linking structure and thus achieving long-lasting adhesion. Second, the high catechin grafting rate can significantly reduce the colloid swelling rate, effectively avoiding the destruction of the adhesive structure caused by colloid swelling and deformation, thereby ensuring the stability of long-term adhesion. The synergistic effect of this triple mechanism—hydrophobic interaction, catechol "mussel-like" adhesion, and NHS active ester or aldehyde chemical bonding—significantly enhances adhesive performance, which has important clinical application significance. However, when the catechol grafting rate is low, it is difficult to achieve high long-term adhesive strength in practical applications.

[0119] This invention utilizes a "dual-solvent stepwise coupling technology" to prepare a polylysine derivative with a high catechin grafting rate, which serves as an adhesive substrate. This substrate is then dissolved and mixed with a multi-arm polyethylene glycol derivative using a specific method to form a mussel-like tissue adhesive. The resulting tissue adhesive can undergo in-situ cross-linking on the tissue surface to form a gel, exhibiting high adhesion, low swelling, and long-lasting bonding characteristics, making it suitable for tissue bonding and sealing applications in various humid environments. First, the high-grafting-rate catechin groups synergistically form interfacial adhesion sites with different mechanical gradients with the two types of adhesive groups, NHS active esters or aldehydes, increasing the number of adhesion sites and enhancing the adhesive strength, thus ensuring the immediate adhesion and sealing performance of the adhesive. Second, the high-catechin-grafting-rate polylysine derivatives and multi-arm polyethylene glycol derivatives crosslink in situ to form a gel with good hydrophobicity, which helps to break through the hydration layer of the tissue surface and contact the tissue through hydrophobic interactions. Finally, while ensuring the adhesiveness and mechanical properties of the colloidal material, the high catechin content can form o-benzoquinone through self-oxidation in a long-term humid environment. This benzoquinone can further couple with the phenolic hydroxyl groups and amino groups of the colloidal material itself or the adhered material to enhance the crosslinking density, improve the stability of the colloidal structure, and avoid excessive swelling, thus significantly enhancing the long-term adhesion between the colloidal material and the tissue.

[0120] In summary, this invention has developed a method for preparing a high-catechin grafting rate adhesive substrate, and constructed a tissue adhesive based on this novel substrate. Through the synergistic effect of hydrophobic interactions, catechin "mussel-like" adhesion, and NHS active ester or aldehyde chemical triple mechanism, key properties such as tissue adhesion are significantly improved.

[0121] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

[0122] The foregoing embodiments and methods described in this invention may vary based on the capabilities, experience, and preferences of those skilled in the art.

[0123] Listing the steps of the method in a certain order in this invention does not constitute any restriction on the order of the method steps.

Claims

1. A method for preparing a high-adhesion, low-swelling mussel-like tissue adhesive, characterized in that, The preparation method includes the following steps: S1. Prepare a polylysine derivative solution containing catechol side groups; S2. Prepare a multi-arm polyethylene glycol derivative solution; S3. Mix the polylysine derivative solution containing catechol side groups and the multi-arm polyethylene glycol derivative solution to obtain the tissue adhesive; The method for preparing the polylysine derivative containing catechol side groups includes the following steps: (1) Dissolve catechol acid in the organic phase, then add NHS first, stir until dissolved and mixed, then add EDC·HCl, stir to react, and obtain catechol-NHS intermediate solution; (2) Dissolve polylysine or its salt in an aqueous phase, and adjust the pH value to 5.5-7.4 using an alkaline solution to obtain a polylysine or its salt solution, wherein the molar ratio of the repeating unit in the catechol acid and polylysine or its salt is 0.05-0.8:1; (3) Add the intermediate solution obtained in step (1) to the polylysine or its salt solution obtained in step (2), and use an alkaline solution to maintain the pH of the reaction system at 4.5-6.5 to obtain a polylysine derivative containing catechol side groups.

2. The preparation method according to claim 1, characterized in that, The catechin acid is selected from one or more of 3,4-dihydroxyphenylpropionic acid, 3,4-dihydroxybenzoic acid, 3,4-dihydroxyphenylacetic acid, 2,3-dihydroxybenzoic acid, and 3,4-dihydroxycinnamic acid; And / or, the polylysine is one or more of ε-polylysine, poly-L-lysine, hyperbranched polylysine, and dendritic polylysine.

3. The preparation method according to claim 1, characterized in that, The multi-arm polyethylene glycol derivative is a functionalized multi-arm polyethylene glycol, wherein the number of arms of the multi-arm polyethylene glycol is 2-8; And / or, the multi-arm polyethylene glycol derivative is a multi-arm polyethylene glycol NHS active ester or a multi-arm polyethylene glycol aldehyde derivative; And / or, the weight-average molecular weight of the multi-arm polyethylene glycol is 5~20kDa; And / or, the end groups of the multi-arm polyethylene glycol NHS active ester include one or more of succinimide nonanoate, succinimide hexanoate, succinimide carbonate, succinimide acetate, succinimide glutarate, and succinimide succinate. And / or, the end groups of the multi-arm polyethylene glycol aldehyde derivative include one or both of butyraldehyde and o-phthalaldehyde.

4. The preparation method according to claim 1, characterized in that, In step S1, the concentration of the polylysine derivative containing the catechol side group in the solution is 30-300 mg / mL; And / or, in step S1, the solvent used for the solution is phosphate buffer, Tris buffer, sodium bicarbonate solution or sodium tetraborate solution; And / or, in step S1, the pH of the solvent is 9.0-12.6; And / or, in step S2, the concentration of the multi-arm polyethylene glycol derivative in the solution is 100-300 mg / mL; And / or, in step S2, the solvent used for the solution is a phosphate buffer, a phosphate solution, a hydrochloric acid solution, or an acetic acid solution; And / or, in step S2, the pH of the phosphate buffer solution is 5.0-7.4; the pH of the phosphate solution, hydrochloric acid solution, or acetic acid solution is 5.0-6.5; And / or, in step S3, the volume ratio of the polylysine derivative solution containing catechol side groups to the multi-arm polyethylene glycol derivative solution is 1:0.8-3.

5. The preparation method according to claim 1, characterized in that, In step (1), the organic phase is selected from one or more of DMSO, DMF, 1,4-dioxane, THF, NMP, and DMAC; And / or, in step (1), the mass concentration of the catecholic acid in the organic phase is 10-200 mg / mL; And / or, in step (1), the molar ratio of the catecholic acid and EDC·HCl is 1:0.2-2; And / or, in step (1), the molar ratio of NHS and EDC·HCl is 1:0.2-2; And / or, in step (1), the reaction temperature is 20-30℃ and the reaction time is 5-100min.

6. The preparation method according to claim 1, characterized in that, In step (2), the mass concentration of the polylysine or its salt solution is 10-30 mg / mL; And / or, in step (2), the aqueous phase is water; And / or, in step (2), the reaction temperature is 20-30℃ and the reaction time is 0.5-3h.

7. The preparation method according to claim 1, characterized in that, In steps (2) to (3), the alkaline solution is selected from one or more of sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution, potassium carbonate solution, sodium bicarbonate solution, potassium bicarbonate solution and triethylamine; And / or, in steps (2)-(3), the mass concentration of the alkaline solution is 1-10%; And / or, the preparation method further includes a post-processing step, which includes the following steps: dialysis, centrifugation and drying of the product obtained in step (3) to obtain a purified polylysine derivative containing catechol side groups; And / or, the dialysate used in the dialysis is selected from hydrochloric acid, acetic acid or citric acid; And / or, the concentration of the dialysate is 0.1-0.5 mM.

Citation Information

Patent Citations

  • Catechol side group-containing polylysine derivative as well as preparation method and application thereof

    CN121758742A

  • Preparation method of bisphenol A-coated antigen with polylysine as carrier and application thereof

    CN103048445A

  • Preparation of in-situ gelation anti-swelling enhanced tissue adhesive material

    CN115869456A

  • Antibacterial cationic hydrogel adhesive and preparation method thereof

    CN119656364A